TINJUAN HUKUM ADMINISTRASI NEGARA DALAM BIDANG PENGELOLAAN SAMPAH SEBAGAI PERWUJUDAN PRINSIP GOOD ENVIRONMENTAL GOVERNANCE DI KOTA PEKANBARU - Fitri, Rahmatul; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Waste management by the regional government belongs to the classification ofcompulsory government affairs that are not related to basic services, namely governmentaffairs which are included in the element of the environment. Due to the high population,the increase in public consumption also increased which caused an increase in wasteproblems in the City of Pekanbaru. While, the ability to manage waste in the city ofPekanbaru is less effective in creating good environmental management in the wastemanagement arrangement. Article 22 of Pekanbaru City Regulation Number 8 of 2014explains that waste management related to changing the characteristics, composition andamount of waste by utilizing environmentally friendly technological advancements can bemanaged through a waste treatment facility with the principle or 3R (Reduce, Reuse andRecycle) or integrated waste treatment facilities.The purpose of this study is to find out the responsibilities of local government inwaste, to find out the obstacles faced in waste management and to find out the efforts toovercome obstacles in the field of waste management in Pekanbaru City. This type ofresearch is classified into sociological legal research, namely research that looks at thecorrelation between law and society, so as to be able to reveal the effectiviness of thevalidity of law in society and identify unwritten laws that apply to society. This researchwas conducted at the Environmental and Sanitation Office of Pekanbaru City. Datasources used are primary data and secondary data. While, the data collection techniquesin this study are questionnaires, interviews and literature review.Conclusions can be obtained from the results of research that waste managementin Pekanbaru City places more emphasis on final processing. While for management inthe form of reduce, reuse and recycle there are already garbage banks, compost housesand TPS3R, but the implementation is not optimal. Optimization of waste managementsuch as waste handling and reduction will not function properly if not supported and puttogether. Realizing good governance by involving its 3 main pillars, namely thegovernment, the private sector and the community in waste management will be a veryeffective way to create a clean, neat and healthy environment.Keywords: Local government responsibilities, waste management, goodenvironmental governance.